أثر الروحانية في مكان العمل على الرضا الوظيفي - خشيم مادي محمد شكري; برشاوه عامر (جامعة الوادي University Of Eloued, 2025)
استهدفت الدراسة اختبار أثر روحانية مكان العمل على الرضا الوظيفي لدى العاملين بمؤسسة اتصالات الجزائر – المديرية العملية للاتصالات لولاية الوادي، ولتحقيق الهدف تم تصميم استبانة وزعت على موظفي اتصالات الجزائر حيث استطعنا جمع (35) استمارة صالحة للمعالجة. تمت الاستعانة بمؤشرات إحصائية للوصول الى النتائج تتمثل في المقاييس الإحصائية ، والانحدار الخطي. كما استخدامنا الحزمة الإحصائية (SPSS) الإصدار 22 لاختبار الفرضيات . وقد توصلنا الى أنه يوجد أثر إيجابي لروحانية مكان العمل على الرضا الوظيفي للعاملين بالمؤسسة من خلال ابعادها الثلاث حيث تبيّن أن العمل الهادف كان البُعد الأكثر تأثيرًا، يليه التوافق القيمي ثم الإحساس بالجماعة . "This study aimed to examine the impact of workplace spirituality on job satisfaction among employees of Algeria Telecom – Operational Directorate of Telecommunications in El Oued Province. To achieve this objective, a questionnaire comprising items was developed and distributed to the employees of Algeria Telecom, resulting in the collection of 35 valid responses for analysis. Various statistical tools, including the arithmetic mean, standard deviation, and linear regression, were employed to analyze the data. The SPSS software (version 22) was used to test the study’s hypotheses. The findings revealed a positive effect of workplace spirituality on job satisfaction across its three dimensions. Among these, meaningful work emerged as the most influential factor, followed by value alignment, and then sense of community.
ماستر
Keywords: الروحانية; روحانية مكان العمل; الرضا الوظيفي; بيئة العمل; اتصالات الجزائر; Spirituality; workplace spirituality; job satisfaction; work environment; Algeria Telecom.